Viscous damping of tremor using a wearable robot with an optimized mechanical metamaterial - Suhas Raghavendra Kulkarni; Dino Accoto; Domenico Campolo (Wearable Technologies)
Pathological tremors can often be debilitating to activities of daily living and significantly affect the quality of life. Such tremulous movements are commonly observed in wrist flexion-extension (FE). To suppress this tremor we present a wearable robot (WR) with a customized mechanical metamaterial (MM) as the physical human-robot interface (pHRI). The MM is optimized to conform to the user’s wrist posture and follow the hand’s Cartesian trajectory. This is done to minimize the shear between the pHRI and the user’s skin and consequently improve wearability. This WR is then used to effect a viscous tremor suppression using the velocity of the user’s wrist FE. We present a model for the interaction between the WR and the user with which we develop the viscous damping approach for tremor. This is then evaluated in simulation and using a dedicated test bed. This tremor suppression approach demonstrates an attenuation of 20–30 dB at various tremulous frequencies resulting in significantly lower tremor amplitudes due to the viscous damping.